Spatial variation in human omnivory during the late Holocene in southern South America: an assessment based on transformed isotopic niches mapping - Barrientos, Gustavo; Catella, Luciana; Morales, Natalia Soledad (Frontiers in Environmental Archaeology, 2025)
The aim of this paper is to present and discuss an approach to address the spatial variation in the degree and type of omnivory exhibited by human populations that inhabited the temperate zone of South America east of the Andes (30°-56° S) during the late Holocene. This approach is based on the interpolation mapping of transformed isotopic niches, understood as the position occupied by an individual or group of individuals in a space that results from transforming one or more of the delta (δ) variables that specify the original isotopic niche (e.g., δ15N [‰]) into derived variables such as trophic position (TP). Our results indicate a strong spatial structuring of both transformed isotopic niches and three omnivory categories (OC I, OC II, and OC III), defined by ranges of TP values (i.e., 2.0–2.99; 3.0–3.99; ≥4.0). Among the factors that likely structured spatial variation in the degree and type of omnivory are those characterizing the physical environment (e.g., net primary productivity or NPP, effective temperature or ET) and the biotic environment (e.g., differential distribution of marine biota). Since these factors have confounding effects, it is difficult to distinguish, given our current state of knowledge, which is the most important. For this reason, we conclude that macroecological analyses are needed that go beyond pattern recognition to address the identification and explanation of underlying processes.